PORTFOLIO OPTIMIZATION WITH MOTH FLAME OPTIMIZATION - JASSON (NIM: 10114087), STEFANUS
When creating a portfolio, an investor surely aims to create a portfolio that has the least risk for a set amount of return, this type of portfolio is known as an optimal portfolio. Creating an optimal portfolio is obviously not an easy task thus the need for a tool that can do this arises. This tool is known as portfolio optimization. Markowitz portfolio model will be used for the portfolio optimization and then various constraints will be added into the problem such as buy-in threshold, cardinality constraint, and roundlot. Moth Flame Optimization (MFO) method will be used to solve this optimization problem. Before the method can be used however, it needs to be modified to be able to solve optimization problems that involves round numbers or Mixed Integer Non-Linear Programming (MINLP). The optimal solution that MFO method gives then will be plotted into an efficient frontier plot.